2017
DOI: 10.1161/hypertensionaha.117.09822
|View full text |Cite
|
Sign up to set email alerts
|

Vascular ADAM17 (a Disintegrin and Metalloproteinase Domain 17) Is Required for Angiotensin II/β-Aminopropionitrile–Induced Abdominal Aortic Aneurysm

Abstract: Angiotensin II (AngII)-activated epidermal growth factor receptor (EGFR) has been implicated in abdominal aortic aneurysm (AAA) development. In vascular smooth muscle cells (VSMC), AngII activates EGFR via a metalloproteinase, a disintegrin and metallopeptidase domain 17 (ADAM17). We hypothesized that AngII-dependent AAA development would be prevented in mice lacking ADAM17 in VSMCs. To test this concept, control and VSMC ADAM17 deficient mice were co-treated with AngII and a lysyl oxidase inhibitor, β-aminopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…For example, previous studies have implicated ADAM17 in the regulation of several substrates involved in the pathogenesis of DR including TNFα, TNFRI/II, IL-6R, p75NTR, and ICAM-1 [9,10,[12][13][14][15][16]. Our data are consistent with previous reports showing that ADAM17 contributes to multiple vascular pathologies [28][29][30]. In particular, studies in brain microvascular endothelial cells demonstrated an important contribution of ADAM17 to vascular barrier impairment in response to hypoxia [32].…”
Section: Discussionsupporting
confidence: 92%
“…For example, previous studies have implicated ADAM17 in the regulation of several substrates involved in the pathogenesis of DR including TNFα, TNFRI/II, IL-6R, p75NTR, and ICAM-1 [9,10,[12][13][14][15][16]. Our data are consistent with previous reports showing that ADAM17 contributes to multiple vascular pathologies [28][29][30]. In particular, studies in brain microvascular endothelial cells demonstrated an important contribution of ADAM17 to vascular barrier impairment in response to hypoxia [32].…”
Section: Discussionsupporting
confidence: 92%
“…Expression of ADAM-17 is elevated in human AAA tissue and its deletion inhibits experimental AAA [28]. Pharmacological inhibition of ADAM-17 or vascular smooth muscle cell deficiency of ADAM-17 attenuates AAA formation and rupture induced by AngII [29]. In the current study, both FXII deficiency and FXIIa neutralisation significantly reduced SRA ADAM-17 activity.…”
Section: Discussionsupporting
confidence: 51%
“…Building upon this, deletion of Cav1, which is required for ANG II-induced ADAM17 activation, prevents AAA development in mice (1033). In line with these observations, deletion of VSMC ADAM17 attenuated AAA formation in mice, which is associated with reduction in aortic EGFR activation, oxidative stress, ER stress, and immune cell accumulation (471). An ER stress inhibitor is also effective in preventing ANG II-induced AAA (848).…”
Section: Egfr Toll-like Receptor 4 and Notch Contributing To Aaa Inmentioning
confidence: 55%
“…ApoEϪ/Ϫ mice overexpressing SMC-specific catalase are also protected from early aortic structural remodeling that underlies AAA development, further highlighting the role of SMC-related ROS production in AAA pathophysiology (635). As described below, VSMC ADAM17-deficient mice are also protected from ANG II-induced AAA, and this was associated with reduced oxidative and ER stress in abdominal aorta (471). VSMC KLF4-deficient mice are also protected from ANG II-dependent AAA development.…”
Section: Cell Type Specific Signaling Mechanisms Leading To Aaamentioning
confidence: 88%